Treatment of pelvic fractures in cats with patellar fracture and dental anomaly syndrome (2020)
Objectives: The aim of this study was to describe the treatment and outcome of acetabular and other pelvic fractures in cats with patellar fracture and dental anomaly syndrome (PADS) and to provide advice on how to manage these cases in practice. Methods: Data were collated on cats with PADS that were reported to have sustained pelvic fractures or had fractures or fissures of the pelvis identified on submitted radiographs. The details of the fractures were recorded, in addition to any treatment and outcome information. Results: Of the 215 cases reported with PADS, 58 cats (27%) were found to have pelvic fractures, none of which were known to have resulted from significant trauma. There were 101 fractures in total and of these 15 were treated with surgery, including 10 acetabular fractures, two ilial, two pubic and one ischial fracture. Screw loosening and loss of fracture reduction was seen in four of the surgically treated fractures (two pubic fractures, one ilial and one acetabular fracture). Fourteen cats were euthanased as a direct result of a fracture occurring. While most pelvic fractures healed uneventfully, some cats remained intermittently lame, but it was not always possible to determine the cause of the lameness from the information available and because all cats had concurrent patellar fractures. Conclusions and relevance: Many of the pelvic fractures healed with conservative management. Fractures involving articular surfaces such as acetabular fractures may benefit from surgical stabilisation as surgery may offer the benefits of articular fracture repair with improved joint congruency and a faster return to normal activity